Transições de fase em monocristais de D-Metionina - Melo, Wanessa David Canedo (2012)
In this work we have been investigated the vibrational properties of the D-methionine single crystals using the Raman and Infrared spectroscopies. The Raman spectroscopy measurements were performed under varying hydrostatic pressure from 0 GPa up to 7.0 GPa, indicated two transitions, one around 2.0 GPa and another in 2.5GPa, which were detected by changes of the vibrationals modes of the carboxilic (CO2-), amino (NH3+), CS, CSC, CH2 and CH3, respectively. These vibrationals modes also have been sensitized under low temperatures, whose changes have been helpful to identify the phase transition with the measurements of the infrared scattering from 298K up to 84K. In the measurements of the Raman scattering realized between 298K and 84K, the transition was identified by emerging of the translational mode in 91 cm-1 around 84K. Further, in this work we have been compared changes presented by crystal lattice between D-methionine and L-methionine under extremes conditions of the pressure.